Imaging of posterior tibial tendon dysfunction—Comparison of high-resolution ultrasound and 3 T MRI. Issue 9 (September 2015) - Arnoldner, Michael A.; Gruber, Michael; Syré, Stefanie; Kristen, Karl-Heinz; Trnka, Hans-Jörg; Kainberger, Franz; Bodner, Gerd
Highlights: 18 MHz high-resolution ultrasound appears to be slightly more accurate than 3 T MRI in the diagnosis of PTTD. High-resolution ultrasound is recommended as an initial diagnostic tool. Long-lasting PTT discomfort may require MRI. Other pathologies can mimic PTTD. Abstract: Purpose: Posterior tibial tendon dysfunction is the most common cause of acquired asymmetric flatfoot deformity. The purpose of this study was to determine and compare the diagnostic value of MRI and high-resolution ultrasound (HR-US) in posterior tibial tendon dysfunction (PTTD), and assess their correlation with intraoperative findings. Materials and methods: We reviewed 23 posterior tibial tendons in 23 patients with clinical findings of PTTD (13 females, 10 males; mean age, 50 years) with 18 MHz HR-US and 3 T MRI. Surgical intervention was performed in nine patients. Results: HR-US findings included 2 complete tears, 6 partial tears, 10 tendons with tendinosis, and 5 unremarkable tendons. MRI demonstrated 2 complete tears, 7 partial tears, 10 tendons with tendinosis, and 4 unremarkable tendons. HR-US and MRI were concordant in 20/23 cases (87%). Image findings for HR-US were confirmed in six of nine patients (66.7%) by intraoperative inspection, whereas imaging findings for MRI were concordant with five of nine cases (55.6%). Conclusion: Our results indicate that HR-US can be considered slightly more accurate than MRI in the detection of PTTD.